Neuroactive steroids, their precursors, and polar conjugates during parturition and postpartum in maternal and umbilical blood: 1. Identification and simultaneous determination of pregnanolone isomers - Hill, M; Parízek, A; Bicíková, M; Havlíková, H; Klak, J; Fait, T; Cibula, D; Hampl, R; Cegan, A; Sulcová, J; Stárka, L (The Journal of steroid biochemistry and molecular biology, 2000)
A rapid method for the identification and measurement of four pregnanolone isomers and their polar conjugates in human plasma was developed using a simple quadrupole GC/MS system with electron impact ionization. Steroid levels were measured in the plasma of 13 and three women at delivery with subarachnoidal and epidural analgesia, respectively, and in corresponding samples of umbilical plasma. A good correlation (r=0.94, P<0.001, n=8) was found between the allopregnanolone in maternal plasma determined by GC/MS and that measured by RIA. Epipregnanolone (3beta-hydroxy-5beta-pregnan-20-one) was identified and measured for the first time in human plasma; its concentration in both maternal and umbilical plasma was much lower than that of other pregnanolone isomers. The levels of 3beta-hydroxy-pregnanolone isomers were significantly higher in the umbilical plasma than in the maternal plasma, while the differences in 3alpha-hydroxy-isomers were insignificant. The differences in conjugates were insignificant except in the case of allopregnanolone, the levels of which were lower in umbilical plasma. In all of the pregnanolone isomers, a significantly lower conjugated/unconjugated steroid ratio was found in the umbilical plasma than in the maternal plasma. The possible role of the sulfatation of pregnanolone isomers around parturition is discussed.
Keywords: Pregnanolone; Adult; Pregnancy; lidé; Humans; plynová chromatografie s hmotnostně spektrometrickou detekcí; novorozenec; poporodní období; pregnanolon; Stereoisomerism; Labor, Obstetric; Fetal Blood; fetální krev; porodní děj; Gas Chromatography-Mass Spectrometry; dospělí; stereoizomerie; ženské pohlaví; těhotenství; Female; Postpartum Period; Infant, Newborn